P14.51 Can patients with a suspected high-grade glioma receive tumor treatment during pregnancy safely?. (9th September 2021) - van der Vegt, A N; de Vries, R; Osinga, J; Grun, N; Postma, T J; de Haan, P F; van Linde, M E; Vandertop, W P; Schuur, M; Kouwenhoven, M C M
Abstract: BACKGROUND: Diagnosis of a glioma during pregnancy has ethical and medical dilemmas; treatment of the mother may harm the unborn child, but a too conservative approach towards tumor treatment can compromise the survival of the mother. In patients with a suspected high-grade glioma, postponing tumor treatment is undesirable. We collected published cases to describe the given treatments during pregnancy and the outcomes for mother and child. METHODS: From Pubmed, Embase and Web of Science, 122 cases were extracted from 65 reports published between 1999 and 2020. We added 7 cases from our center. Cases came from: North-America (54/129), Europe (47/129), Asia (13/129), Middle-East (3/129) and one from Oceania and Africa each; 10 cases were from an unspecified country. The data were analysed with descriptive statistics. RESULTS: The median age of the pregnant women was 30 (range 17–48) years; at the time of publication 42% of mothers had deceased. Most frequent symptoms at presentation were high intracranial pressure (35%), seizures (30%) or focal deficits (19%). Patients were diagnosed in each phase of the pregnancy - 30% in the first, 35% in the second and 35% in the last trimester. Twenty-two women decided to terminate the pregnancy (North America 9; Europe 9; international unspecified, Africa, Asia and Middle-East each one case). In sixty-seven percent of women, tumors were operated while pregnant, 70% of those were planned surgery, while in 30% surgery was in performed in an emergency setting. Most women received a resection. In 6 patients tumor surgery was combined with a caesarian section. Histological diagnosis of the tumor was available in 112 patients: anaplastic oligodendroglioma (n=10), anaplastic astrocytoma (n=30), glioblastoma (n=66) or high-grade glioma NOS (n=6). In 10 patients there was a suspected high grade glioma based on MRI imaging. Only 20 patients were treated after surgery whilst still pregnant with either radiotherapy (15/20, 75%), chemotherapy (2/20, 10%) or a combination of radiotherapy and chemotherapy (3/20, 15%) Other patients received additional treatment after delivery (109/129; 84%). Delivery method was a caesarian section in 60% and vaginal delivery in 21%- in 19% delivery method was not described. In 63% of cesarean sections were brought forward either because of rapid maternal deterioration or to enable maternal treatment after delivery. In 92% a healthy child was born, 7% had a intrauterine fetal death and 1% the child was stillborn. None of the patients who experienced intrauterine fetal death had received radio- or chemotherapy during pregnancy. CONCLUSIONS: The majority of pregnant women continue their pregnancy when facing a diagnosis of a high grade glioma. Tumor surgery seemed safe during pregnancy. No adverse events were reported in the limited patients who received radiotherapy (n=15) during pregnancy. For chemotherapy we could not draw any conclusions.